Secularism and Its Challenges to Traditional Religious Beliefs and Practices - Abdul Rahim, Adibah (2007)
The Western influence on the Muslim world was so complex covering all facets of man’s life. From the political, military, and economic domination, the West impinged further on religious and intellectual life by producing various modern scientific and philosophical theories. Therefore, the Muslim world had been confronted by the assault of an alien civilization which has challenged the very tenets of Islamic worldview. Secularism is the most serious challenge posed by the West. Its main ideology is to expel religion from the practical aspect of man’s life and to liberate him from the religious and metaphysical values. Under secularism, man has the rights to stipulate a system that is suitable to him, thus, usurped the divine authority of God. As a result, the culture brought about by secularism was entirely materialistic which is cut off from Divine, transcendent or supernatural principles and does not refer to and is isolated from Revelation. The idea of secularism is strongly upheld and is continuously affirmed by most scholars all over the world. They tend to give less emphasis on transcendental values and represent the emergence of a culture largely secular in character. In terms of its intensity and scope as well as its discernable effects upon people’s mind, the repercussion of secularism is so pervasive and universal. It gives a great impact on the individual and family lives, as well as educational, political, economics, and social-cultural realm. Subsequently, we live in a time of crisis of civilization, brought on in particular by the challenge of secularism. This paper tries to explore what are the main principles of secularism, why secularism is seen as a threat and dangerous, and how it has posed its challenges to the minds of individuals as well as society at large. It is hoped that this paper can give a meaningful and profound treatment of the intellectual development in Islamic thought.